Airway models in a pandemic: suitability of models in modeling SARS-CoV-2 - Teo, Andrew (2022)
In a global pandemic involving respiratory pathogens such as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), intensified scientific research is required to delineate pathways involved in infectivity, transmissibility, and pathogenicity of the causative pathogen. SARS-CoV-2, the causative agent of Coronavirus Disease 2019 (COVID-19), is highly contagious and significantly threatens public health. This single-stranded positive RNA virus consisting of approximately 30 kb genome size virus is from the same Sarbercovirus subgenus as SARS-CoV [1]. While most people who are infected exhibit only mild–moderate respiratory symptoms including cough and dysgeusia, some may develop acute respiratory distress syndrome. Postmortem lungs of COVID-19 patients showed severe pulmonary damage and abundant inflammatory infiltrates [2]. Given the urgent need to study the pathogenesis of this disease and to test the efficacy of potential therapeutics, several in vitro and in vivo models have been developed. Herein, the use and limitations of two-dimensional (2D) and animal models in COVID-19 research are discussed, followed by a review on the use of lung organoids in advancing our knowledge on COVID-19 pathogenesis.